Edukasi pencegahan pernikahan dini dan bahaya stunting: Studi kasus seminar edukasi di mts al fathoni desa poncokusumo kabupaten malang - Nurisshofa, Ahmad (Maliki Interdisciplinary Journal, 2025)
Stunting and early marriage are two significant issues in Indonesia, particularly in Poncokusumo Village, Malang Regency, East Java. With an early marriage prevalence of 11.3% in 2022 and a stunting rate of 21.3% in 2023, these issues require special attention. Research indicates that early marriage is directly linked to an increased risk of giving birth to stunted children. Mothers who marry at an early age are 1.5 times more likely to give birth to children with stunting. The seminar "Prevention of Early Marriage and the Dangers of Stunting" was held at MTs Al Fathoni Poncokusumo. The purpose of this seminar was to enhance students’ understanding of the impact of early marriage and stunting, as well as to provide knowledge about the ideal age for marriage in accordance with Law No. 16 of 2019. This seminar employed a qualitative approach, including interviews and participatory observation, to assess changes in participants’ knowledge and attitudes. It is hoped that this seminar will educate the younger generation about the dangers of early marriage and stunting while also helping to prevent these issues in their communities. Thus, this activity not only offers theoretical benefits for the development of educational studies but also provides practical benefits by increasing public awareness of child nutrition and reproductive health.